POLA PEMBERDAYAAN MASYARAKAT DI HULU SUB DAERAH ALIRAN SUNGAI MIU (KASUS PENERAPAN PROGRAM SCBFWM DI DESA BOLADANGKO KECEMATAN KULAWI KABUAPTEN SIGI PROVINSI SULAWESI TENGAH) - Idhar, Moh; Golar, Golar; Sudhartono, Arif (Universitas Tadulako, 2017)
Sub Watershed of Miu is located in the district of Sigi with an area of 70,494.5 ha, part of area has become a critical area. Community manage the land solely because of economic factors to meet the needs of daily life without thinking about how to manage the land to remain productive and may be used in a relatively long time. Programs of Strengthening Community-Based Forest and Watershed management (SCBFWM) is a community development programs around the sub watershed Miu that aims to reduce the rate of degradation, and improve watershed function. This study aim to assess how the form community development programs is implemented and mentoring methods and constraints faced in the implementation of community development activities in the SCBFWM program. This research was conducted in the upper sub-watershed of Miu, in Boladangko Village, Sub-District of Kulawi, District of Sigi, Central Sulawesi Province for two months (February to April 2014) using surveys and interviews. The interview guide addressed to the 15 respondents consisting of activity mentor (field facilitators), the community member and members of farmer groups. Complement information and confirmation of data from respondents using snowball sampling method. Research support tools such as tape recorders and cameras as well as stationery. The results showed that the pattern of community development programs implemented SCBFWM include the establishment of farmer groups, farmer groups training in self-reliance, sustainable socialization, rehabilitation, development and improvement of farming institutional structures and assistance to farmer group. Mentoring method which is implemented by SCBFWM emphasis change in mindset and a change of activity-based economic improvement of farmers. The main obstacle faced SCBFWM is the lack of funding support from various parties in the implementation of community development programs and lack of community participation in the monthly meetings.